2021
DOI: 10.3389/fmicb.2021.631254
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics, Prebiotics, and Synbiotics in the Elderly: Insights Into Their Applications

Abstract: Elderly people are an important part of the global population who suffer from the natural processes of senescence, which lead to changes in the gut microbiota composition. These modifications have a great impact on their quality of life, bringing a general putrefactive and inflammatory status as a consequence. Some of the most frequent conditions related to this status are constipation, undernutrition, neurodegenerative diseases, susceptibility to opportunistic pathogens, and metabolic disbalance, among others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 103 publications
0
26
0
1
Order By: Relevance
“…Recently, other strains in the genus Lactobacillus have shown to produce B12-type compounds, including Lactobacillus coryniformis isolated from goat milk [91], Lactobacillus plantarum from kanjika or Japanese pickles [92,93], Lactobacillus rossiae from sourdoughs [94] and Lactobacillus fermentum CFR 2195 from breast-fed healthy infants' fecal sample [95], but further research is needed to elucidate their role in active B12 production. The addition of vitamin B12-producing LABs into fermented foods could potentially have two advantages: on one hand increase vitamin B12 concentrations, and on the other hand exhibit healthy properties, since in the elderly there is a general decrease in diversity exhibition in species of Lactobacilli [96].…”
Section: Novel Bacteria and In Situ Fortificationmentioning
confidence: 99%
“…Recently, other strains in the genus Lactobacillus have shown to produce B12-type compounds, including Lactobacillus coryniformis isolated from goat milk [91], Lactobacillus plantarum from kanjika or Japanese pickles [92,93], Lactobacillus rossiae from sourdoughs [94] and Lactobacillus fermentum CFR 2195 from breast-fed healthy infants' fecal sample [95], but further research is needed to elucidate their role in active B12 production. The addition of vitamin B12-producing LABs into fermented foods could potentially have two advantages: on one hand increase vitamin B12 concentrations, and on the other hand exhibit healthy properties, since in the elderly there is a general decrease in diversity exhibition in species of Lactobacilli [96].…”
Section: Novel Bacteria and In Situ Fortificationmentioning
confidence: 99%
“…These microorganisms are characterized by the ability to colonize various environments in the human body, in particular the intestines, where they play a key role in stimulating the passage of intestinal epithelial cells and ensure the proper development of commensal microorganisms. Prebiotics are food ingredients that selectively influence the development of a specific group or type of microorganism with probiotic properties in the gastrointestinal tract [ 121 , 122 , 123 ].…”
Section: How To Restore the Symbiosis Of The Gut Microbiota?mentioning
confidence: 99%
“…The last group are symbiotic, i.e., a combination of pro and prebiotics, which together show a synergistic effect influencing the development of normal intestinal microbiota. In addition, it has been shown that they can participate in reducing the concentration of undesirable toxins or metabolites in the human body, and are also involved in the processes of preventing putrefactive reactions in the intestines and the formation of constipation or diarrhea [ 121 , 122 , 123 ].…”
Section: How To Restore the Symbiosis Of The Gut Microbiota?mentioning
confidence: 99%
“…Elderly people, in general, suffer from changes in the gut microbiota composition, leading to a gradual shift toward a reduced bacterial diversity. This implies a decline in valuable microorganisms that exert beneficial health effects, such as protection against pathogens and presenting anti-inflammatory properties [219]. Some very interesting reports have been published on the antioxidant and anti-inflammatory properties of different synbiotics in naturally (C57BL/6 mice), genetically (SAMP8 mice), or chemically-induced (d-gal-induced Sprague Dawley rats or C57BL/6 mice) aged rodent models.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%